2015
DOI: 10.1016/j.foodchem.2014.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of folic acid in food hydrocolloids through nanospray drying and electrospraying for nutraceutical applications

Abstract: In this work, two different technologies (electrospraying and nanospray drying) were evaluated for encapsulation of folic acid using a whey protein concentrate (WPC) matrix and a commercial resistant starch. The morphology of the capsules, molecular organization of the matrices, encapsulation efficiency, and stability of folic acid within the capsules under different storage conditions and upon thermal exposure were studied. Results showed that spherical submicro-and microcapsules were obtained through both te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(97 citation statements)
references
References 27 publications
4
77
0
3
Order By: Relevance
“…Under these experimental conditions, folic acid-loaded zein nanoparticles displayed a mean size after reconstitution of about 200 nm with a negative zeta potential of À24 mV and a low polydispersity index ( Table 1). The folic acid content was close to 54 mg/mg nanoparticles, which is approximately 3-times higher than the payload reported by Perez-Masi a and collaborators who used nano-and microcapsules from either whey protein or starch [34].…”
Section: Discussionmentioning
confidence: 57%
“…Under these experimental conditions, folic acid-loaded zein nanoparticles displayed a mean size after reconstitution of about 200 nm with a negative zeta potential of À24 mV and a low polydispersity index ( Table 1). The folic acid content was close to 54 mg/mg nanoparticles, which is approximately 3-times higher than the payload reported by Perez-Masi a and collaborators who used nano-and microcapsules from either whey protein or starch [34].…”
Section: Discussionmentioning
confidence: 57%
“…The encapsulation was traced down to the favourable interactions between the protein and folic facilitating incorporation of the vitamin. Empirical results showed that whey protein concentrate serve better than the commercial resistant starch for folic acid stability (Pérez-Masiá et al 2015). This study assessed the oxygen-scavenging potential of an edible whey protein isolate film impregnated with ascorbic acid.…”
Section: Encapsulation Edible Coating Active Packaging Delivery Symentioning
confidence: 99%
“…The shape and type of capsule formed are influenced by procedure of emulsification with core and coating materials and drying process (Rosenberg et al, 1990). Recently, Pérez-Masiá et al (2015) reported that spray drying is very efficient for the production of nanocapsule of folic acid in food hydrocolloids.…”
Section: Introductionmentioning
confidence: 99%